2020
DOI: 10.3390/nano10030569
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Selective Surface Plasmon Resonance Response Based on a Reduced Graphene Oxide–Polyamidoamine Nanocomposite for Detection of Dengue Virus E-Proteins

Abstract: Dengue viral infection is one of the most common deadliest diseases and has become a recurrent issue for public health in tropical countries. Although the spectrum of clinical diagnosis and treatment have recently been established, the efficient and rapid detection of dengue virus (DENV) during viremia and the early febrile phase is still a great challenge. In this study, a dithiobis (succinimidyl undecanoate, DSU)/amine-functionalized reduced graphene oxide-–polyamidoamine dendrimer (DSU/amine-functionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 69 publications
(66 reference statements)
0
50
0
Order By: Relevance
“…A composite of reduced graphene oxide and polyamidoamine (PAMAM) dendrimers is described for the detection of the E-proteins of the serotype 2 of dengue virus (DENV 2). The detection format consisted of an immunoassay in which monoclonal antibodies were immobilized on self-assembled, dithiobis (succinimidyl undecanoate) amine-activated layers [ 50 ]. The characterization of analytical parameters involved the determination of affinity-binding constants, detection accuracy, and figure of merit values for the minimum E-proteins’ concentration (0.08 pM) while the assay selectivity was tested against E- proteins of Zika virus ( Figure 10 ).…”
Section: Biosensing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A composite of reduced graphene oxide and polyamidoamine (PAMAM) dendrimers is described for the detection of the E-proteins of the serotype 2 of dengue virus (DENV 2). The detection format consisted of an immunoassay in which monoclonal antibodies were immobilized on self-assembled, dithiobis (succinimidyl undecanoate) amine-activated layers [ 50 ]. The characterization of analytical parameters involved the determination of affinity-binding constants, detection accuracy, and figure of merit values for the minimum E-proteins’ concentration (0.08 pM) while the assay selectivity was tested against E- proteins of Zika virus ( Figure 10 ).…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…Inset: SPR time response upon introduction of 0.08 to 1 pM of dengue virus (DENV 2) E-proteins. Adapted with permission from Omar et al [ 50 ] Copyright © (2020) MDPI (under the terms and conditions of the Creative Commons CC BY License).…”
Section: Figurementioning
confidence: 99%
“…Direct methods, exploiting graphene nanotechnology, for the rapid virus detection, have been only marginally investigated in the past, and no critical discussion has been reported in successive literature reviews [ 96 , 97 ].…”
Section: Graphene-based Strategies In the Diagnosis Of Viral Diseamentioning
confidence: 99%
“…It was demonstrated that SPR sensor has the ability to detect pregnancy associated plasma protein A2, which is a metalloproteinase that plays multiple roles in fetal development and postnatal growth [35]. Several studies were reported on using SPR sensor as a new strategy to detect influenza nucleoprotein [36], avian influenza A H7N9 virus [37], maize chlorotic mottle virus [38], herpes simplex virus (HSV) [39], cancer cell line (HeLa cells) with biomarker Rhodamine 6G related to cancer tumors [40], nonstructural protein 1 of Zika virus [41], non-human pathogen feline calicivirus (FCV) [42], and dengue virus (DENV) [43][44][45][46].…”
Section: The Importance Of Spr Biosensors In the Medical Diagnosismentioning
confidence: 99%